2022
DOI: 10.1002/adsu.202100495
|View full text |Cite
|
Sign up to set email alerts
|

From Corn Husks to Scalable, Strong, Transparent Bio‐Plastic Using Direct Delignification‐Splicing Strategy

Abstract: Biomass‐based plastics (BPs), produced from natural polymers using a bottom‐up strategy, have been used to alleviate the environmental pollution caused by petrochemical‐based plastics (PCPs). Such BPs, however, typically require complex manufacturing processes, resulting in higher costs and reduced eco‐friendly features. Herein, a delignification‐splicing‐based strategy without adhesives for directly converting corn (Zea mays L.) husks to corn husk‐based plastic (CHP) is described. During this process, lignin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…The X-ray diffraction patterns of the W-BPs (Figure b) indicated that, compared with natural wood, the crystalline structure of cellulose I was well maintained under different delignification conditions. , The crystallinity index can be calculated according to the Segal method, and the crystallinities of NaOH-H 2 O 2 -W-BP and NaClO 2 -W-BP are 73 and 62%, respectively, revealing that more amorphous cellulose was removed from NaOH-H 2 O 2 -W-BP than from NaClO 2 -W-BP. Notably, the ratio of the (200) to (110) crystal plane of NaOH-H 2 O 2 -W-BP is apparently larger than those of NW and NaClO 2 -W-BP, indicating that more hydrophobic (200) crystal planes of cellulose are exposed in NaOH-H 2 O 2 -W-BP .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The X-ray diffraction patterns of the W-BPs (Figure b) indicated that, compared with natural wood, the crystalline structure of cellulose I was well maintained under different delignification conditions. , The crystallinity index can be calculated according to the Segal method, and the crystallinities of NaOH-H 2 O 2 -W-BP and NaClO 2 -W-BP are 73 and 62%, respectively, revealing that more amorphous cellulose was removed from NaOH-H 2 O 2 -W-BP than from NaClO 2 -W-BP. Notably, the ratio of the (200) to (110) crystal plane of NaOH-H 2 O 2 -W-BP is apparently larger than those of NW and NaClO 2 -W-BP, indicating that more hydrophobic (200) crystal planes of cellulose are exposed in NaOH-H 2 O 2 -W-BP .…”
Section: Resultsmentioning
confidence: 97%
“…40−42 The X-ray diffraction patterns of the W-BPs (Figure 2b) indicated that, compared with natural wood, the crystalline structure of cellulose I was well maintained under different delignification conditions. 43,44 The crystallinity index can be calculated according to the Segal method, 38 and the crystallinities of NaOH-H 2 O 2 -W-BP and NaClO 2 -W-BP are 28 Furthermore, the container with NaOH-H 2 O 2 -W-BP and ethanol was vigorously shaken to obtain a suspension of cellulose nanomaterials. Figures 2c and S5 show the TEM images of the above cellulose nanomaterials.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Compared with that of silver porous hollow spheres [34], the ratio of intensities of the peaks (111) to (200) recorded in Figure 1 is larger, might further indicating the 1D growth along (111) direction. Figure 2 shows the scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images [37][38][39][40] of the Ag nanowires [10,25,26]. Figure 2a shows the Figure 2 shows the scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images [37][38][39][40] of the Ag nanowires [10,25,26].…”
Section: Morphology and Phase Of Ag Nanowiresmentioning
confidence: 99%
“…Figure 2 shows the scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images [37][38][39][40] of the Ag nanowires [10,25,26]. Figure 2a shows the Figure 2 shows the scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images [37][38][39][40] of the Ag nanowires [10,25,26]. Figure 2a shows the overall morphology of the Ag nanowires with lengths of up to tens of micrometers.…”
Section: Morphology and Phase Of Ag Nanowiresmentioning
confidence: 99%
“…Transparent wood has potential applications in energy-efficient buildings and electronic devices, owing to its high optical transmittance, low thermal conductivity, and high safety [ 1 , 2 ]. Various delignification methods have been developed to remove lignin from wood, including sodium chlorite (NaClO 2 ) [ 1 ], sodium hypochlorite (NaClO) [ 3 ], sodium hydroxide/sodium thiosulfate (NaOH/NaS 2 O 3 ) [ 2 ], and hydrogen peroxide (H 2 O 2 ) steaming [ 4 ], all of which provide well-preserved cellulose skeletons for transparent wood through infiltration with epoxy resin, PMMA, PVA, PLA, and PVP [ 5 , 6 , 7 , 8 , 9 ]. Previous studies have demonstrated that H 2 O 2 steaming, a green and highly efficient delignification method, provides a wood skeleton with a very low content of residual lignin, which could be used further as a skeleton for transparent wood [ 4 , 10 ], catalyst supports [ 11 ], solar evaporation generators [ 12 ], and bioplastics [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%